Pemerintah Daerah dalam Menyusun Laporan Penyelenggaraan Pemerintahan Daerah - M. Harry Mulya Zein; Gevin Wukt Wakim; Sisca Septiani (Universitas 17 Agustus 1945 Semarang, 2022)
The background of this research focuses on the complexity of the relationship between central and local governments in the context of governance in Indonesia. One manifestation of this decentralization concept is the Local Government Implementation Report (LPPD), which is a key instrument in ensuring local government accountability. This research was motivated by problems such as lack of complete data, delays in collection, and budget limitations in the preparation of LPPD. The purpose of this study is to understand the extent of coordination of the local government of Ambon City in the practice of LPPD, as well as the supporting and inhibiting factors of the process. The method used is qualitative, with primary data from interviews and secondary data from documentation. The results show that effective coordination is a key element in the preparation of LPPD Ambon City. Key factors in coordination include effective communication, awareness of the importance of coordination, commitment from relevant parties, participant competence, and coordination incentives. This study offers recommendations to improve the effectiveness of coordination in the preparation of LPPD to support local government development goals and community welfare.